Breast cancer brain metastases genomic profiling identifies alterations targetable by immune-checkpoint and PARP inhibitors - A. Giannoudis; E. S. Sokol; T. Bhogal; S. H. Ramkissoon; E. D. Razis; R. Bartsch; J. A. Shaw; K. McGregor; Alison Clark; R.S.P. Huang; C. Palmieri (npj Precision Oncology)
Abstract Understanding the genomic landscape of breast cancer brain metastases (BCBMs) is key to developing targeted treatments. In this study, targetable genomic profiling was performed on 822 BCBMs, 11,988 local breast cancer (BC) biopsies and 15,516 non-central nervous system (N-CNS) metastases (all unpaired samples) collected during the course of routine clinical care by Foundation Medicine Inc (Boston, MA). Clinically relevant genomic alterations were significantly enriched in BCBMs compared to local BCs and N-CNS metastases. Homologous recombination deficiency as measured by BRCA1/2 alteration prevalence and loss-of-heterozygosity and immune checkpoint inhibitor (ICI) biomarkers [Tumor mutation burden (TMB)-High, Microsatellite instability (MSI)-High, PD-L1/L2)] were significantly more prevalent in BCBM than local BC and N-CNS. High PD-L1 protein expression was observed in ER-negative/HER2-negative BCBMs (48.3% vs 50.0% in local BCs, 21.4% in N-CNS). Our data highlights that a high proportion of BCBMs are potentially amenable to treatment with targeted therapeutic agents including PARP inhibitors and ICIs.